Prescription trends of antiseizure medications before and during the COVID-19 pandemic - Lavu, Alekhya; Janzen, Donica; Aboulatta, Laila; Peymani, Payam; Haidar, Lara; Desrochers, Brianne; Alessi-Severini, Silvia; Eltonsy, Sherif (Frontiers in Neurology, 2023)
Introduction Given the lack of evidence on how the COVID-19 pandemic impacted antiseizure medication (ASM) use, we examined the trends of ASMs before and during COVID-19. Methods We conducted a population-based study using provincial-level health databases from Manitoba, Canada, between 1 June 2016 and 1 March 2021. We used interrupted time series autoregressive models to examine changes in the prevalence and incidence of ASM prescription rates associated with COVID-19 public health restrictions. Results Among prevalent users, the COVID-19 pandemic led to a significant increase in new-generation ASMs with a percentage change of 0.09% (p = 0.03) and a significant decrease in incidence use of all ASMs with a percentage change of −4.35% (p = 0.04). Significant trend changes were observed in the prevalent use of new-generation ASMs (p = 0.04) and incidence use of all (p = 0.04) and new-generation ASMs (p = 0.02). Gabapentin and clonazepam prescriptions contributed 37% of prevalent and 54% of incident use. Conclusion With the introduction of public health measures during COVID-19, small but significant changes in the incident and prevalent use of ASM prescriptions were observed. Further studies are needed to examine whether barriers to medication access were associated with potential deterioration in seizure control among patients. Conference presentation The results from this study have been presented as an oral presentation at the 38th ICPE, International Society of Pharmacoepidemiology (ISPE) annual conference in Copenhagen.